A 300-year surge history of the Drangajökull ice cap, northwest Iceland, and its maximum during the 'Little Ice Age'. (July 2015) - Brynjólfsson, Skafti; Schomacker, Anders; Guðmundsdóttir, Esther Ruth; Ingólfsson, Ólafur
Over the last 300 years, each of the three surge-type outlet glaciers of the Drangajökull ice cap in northwest Iceland has surged 2–4 times. There is valuable historical information available on the surge frequencies since the 'Little Ice Age' (LIA) maximum because of the proximity of the surging outlets, Reykjarfjarðarjökull, Leirufjarðarjökull and Kaldalónsjökull, to farms and pastures and monitoring of these glaciers since 1931. We have reconstructed the surge history of the Drangajökull ice cap, based on geomorphological mapping, sedimentological studies and review of historical records. Geomorphological mapping of the glacier forefields reveals twice as many end moraines as previously recognized. This indicates a higher surge interval than earlier perceived. A clear relationship between the surge interval and climate cannot be established. Surges were observed more frequently during the 19th century and the earliest 20th century compared with the relatively cool 18th century and the late 20th century, possibly reflecting a lack of information rather than a long quiescent phase of the glaciers. We have estimated the magnitude of the maximum surge events during the LIA by reconstruction of Digital Elevation Models (DEMs) that can be compared with modern DEMs. As reference points for the digital elevation modelling, we used the recently mapped lateral moraines and historical information on the exposure timing of nunataks . During the LIA maximum surge events, the outlet glaciers extended 3–4 km further down-valley than at present. Their ice volumes were at least 2–2.5 km 3 greater than in the beginning of the 21st century.